Commercial Gold Complexes Supported on Functionalised Carbon Materials as Efficient Catalysts for the Direct Oxidation of Ethane to Acetic Acid - Ribeiro, Ana P. C. (2022)
UIDB/00100/2020 UIDP/00100/2020 LA/P/0056/2020 IST-ID/119/2018 SFRH/BD/146426/2019 CEEC-INST/00102/2018 UIDB/50006/2020 UIDP/50006/2020 Base-UIDB/50020/2020 Programmatic-UIDP/50020/2020